Manajemen Promosi Online Pariwisata Nusa Tenggara Barat (Studi Kasus Badan Promosi Pariwisata Daerah NTB dalam Mengelola Promosi Online Tahun 2013-2014) - , SUCI LUKITOWATI; , Prof. Dr. Nunung Prajarto, M.A ([Yogyakarta] : Universitas Gadjah Mada, 2014)
Since 2010 West Nusa Tenggara Regional Tourism Promotion Board (BPPD NTB has been formed which is responsible towards tourism promotion activities in NTB. This organization has vigorously done tourism promotion, managed to bring in 1.1 million tourists in the last 2012. This succession is increased by targeting tourist arrivals about 2 million by the end of 2015. However, the using of cyberspace to maximize the promotion of tourism object is still below the expectation. On the one hand, tourism promotion budget for 2014 was reduced from the previous $ 7 billion to 2 billion. BPPD NTB actually has an online media campaign as the official tourism website, which is able to visit at www.lomboksumbawa.travel. But until now the website is not running well, so it is important to know how to manage it through other communication elements and other aspects. This research uses a case study method. It is known that the management of the website is very weak. It can be seen through the support, resource capacity, the value of usefulness, as well as assess the management of the communication element. The constraint faced is the lack of human resources and the lack of supervision in the control of a third party's performance in managing the website. These constraints caused by a lack of organizational readiness BPPD NTB in terms of human resources. In the first period of stewardship BPPD NTB has no executive element. Readiness of the website is also remind lack due to the focus of NTB's tourism promotion until mid-2014 is a direct promotion instead of online promotion through websites that have been made. In August 2014 online campaign has been worked again. The work forms are revitalization BPPD NTB official website located at www.bppdntb.com, as well as creating a Facebook fan page named BPPD NTB and presenting an application for android based smart phone named Holiday is Lombok Sumbawa.